2019
DOI: 10.3389/fphar.2019.00490
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor Efficacy Assessment of the Sigma Receptor Pan Modulator RC-106. A Promising Therapeutic Tool for Pancreatic Cancer

Abstract: Introduction: Pancreatic cancer (PC) is one of the most lethal tumor worldwide, with no prognosis improvement over the past 20-years. The silent progressive nature of this neoplasia hampers the early diagnosis, and the surgical resection of the tumor, thus chemotherapy remains the only available therapeutic option. Sigma receptors (SRs) are a class of receptors proposed as new cancer therapeutic targets due to their over-expression in tumor cells and their involvement in cancer biology. The main loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Such effect was mirrored by the impairment of proteasome activity (Figure 6), an enzyme involved in the protein homeostasis. This activity was also documented in our previous work focused on the antitumor activity of the hit RC-106 and where we showed its capability to trigger the UPR response machinery (Tesei et al, 2019). Accordingly, the compounds also hamper tumor cell growth starting from the lowest concentrations tested, as evidenced by the proliferation test (Figure 7) showing also a significant induction of cell death (∼50%) at the highest concentration tested (Figure 5).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Such effect was mirrored by the impairment of proteasome activity (Figure 6), an enzyme involved in the protein homeostasis. This activity was also documented in our previous work focused on the antitumor activity of the hit RC-106 and where we showed its capability to trigger the UPR response machinery (Tesei et al, 2019). Accordingly, the compounds also hamper tumor cell growth starting from the lowest concentrations tested, as evidenced by the proliferation test (Figure 7) showing also a significant induction of cell death (∼50%) at the highest concentration tested (Figure 5).…”
Section: Discussionsupporting
confidence: 84%
“…Our medicinal chemistry campaign recently led to the identification of ( E )-4-benzyl-1-[3-(naphthalen-2-yl)but-2-en-1-yl]piperidine (henceforth RC-106 ) ( Figure 1 ). This compound is able to activate terminal unfolded protein response (UPR) and to inhibit proteasome complex activity, through the induction of endoplasmic reticulum stress (ER) (Tesei et al, 2019 ). Moreover, RC-106 possesses a pan-SRs profile—ability to bind both S1R and S2R—and shows a cytotoxic effect against a wide panel of cancer cell lines, all expressing SRs, acting as a proapoptotic drug, which induces a fast triggering of cell death program (Rui et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…To further our understanding of the relationship between SRs and the terminal UPR pathway, we first compared the activity of our compound with that of two well-known ER stress inducers: thapsigargin (TG) a SERCA inhibitor, and bortezomib (BTZ), a known proteasome inhibitor [ 46 ]. The choice of concentrations and exposure time used was based on literature data and on previous results obtained by Real-Time qRT-PCR [ 45 ]. To this purpose, cells were treated with the three molecules and the effect on the expression of ER-stress/terminal UPR markers compared.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, given that tissue distribution in target organs is at the core of the development process because of its direct impact on drug activity, we studied the pharmacokinetic profile of the modulator and evaluated its distribution in the pancreas. Our results showed that RC-106 was 25-fold more concentrated in the pancreas than in plasma, reaching a concentration higher than that required to be effective in all the in vitro experiments [ 45 ]. In light of the above considerations, we used RC-106 as a drug model to investigate the therapeutic role of SRs in activating the terminal UPR, mediated by ER stress induction.…”
Section: Introductionmentioning
confidence: 99%
“…Several S2R antagonists are shown to have beneficial effects in neurodegenerative diseases such as AD and are currently evaluated in clinical trials [150][151][152]. However, S2R agonists also induce neurodegeneration [151] and apoptosis, which makes them attractive as anti-cancer drugs [153]. Therefore, a relatively nonselective S1R agonist, with lower affinity, agonistic activity at S2R may activate the S2R at high doses.…”
Section: Possible Mechanisms For the Bi-phasic Drug Effectmentioning
confidence: 99%